Experimental numerical correlation of the delamination of composite structures subjected to low speed impact - Burgos de la Rosa, Ismael; López-Taboada, Carlos; Castillo-López, Germán; Zabala, Haritz; Aretxabaleta, Laurentzi; García-Sánchez, Felipe (My University, 2017)
In this work, we have analyzed the delamination caused by a low velocity impact on carbon-epoxy laminates made with balanced 0/90 braided fabrics and made by resin infusion. The items have been tested with a fall drop system. The numerical simulation was performed using the Explicit Non-Lineal Finite Element Method (NASTRAN SOL700). Delamination was analyzed using cohesive zone models (CZM). The parameters of the Tvergaard and Hutchinson constitutive law have been defined based on experimental fracture data of the laminate and mechanical properties of the resin used. The results show a good correlation (error<2%) regarding the maximum force, contact time and residual stiffness. The good correlation in evaluating the residual stiffness after impact has special interest since it allows the designer to evaluate the integrity level of a structure that has suffered an impact, generating damage.
Keywords: Composites; Materiales laminados; FEM-explicit; Delamination; CZM